Cycling as Means of Transportation: Consolidating Inequities in the Streets of Cali, Colombia - Mosquera Becerra, María Janeth (Sociedad y Economía, 2016)
The means of transport are decisive for accessibility to places, goods, services andmarkets. Motorized transport means have gained prominence in the world. Through acase study, where interviews and document review are used, forces and processes areidentified and analyzed in different (global, national and local) scales, which have in-fluenced the decision-making process that contribute to the hegemony of motorizedtransport instead of using bicycles as a means of transport in the city of Cali, Colombia.The results show the political and economic nature of built urban environment of whichtransport is part and, more specifically, how struggles for road space, to use the bicycle asa means of transportation in Cali, are a type of class conflict occurring in urban areas, andaffects people who use bicycles as a primary mode of transportation in Cali.